Approaching Dialogue : Talk, interaction and contexts in dialogical perspectives. - Linell, Per (John Benjamins Pub. Co., 1998)
Approaching Dialogue has its primary focus on the theoretical understanding and empirical analysis of talk-in-interaction. It deals with conversation in general as well as talk within institutions against a backdrop of Conversation Analysis, context-based discourse analysis, social pragmatics, socio-cultural theory and interdisciplinary dialogue analysis. People's communicative projects, and the structures and functions of talk-in-interaction, are analyzed from the most local sequences to the comprehensive communicative activity types and genres. A second aim of the book is to explore the possi.